Perancangan User Interface Website Institut Manajemen Wiyata Indonesia - Ardiles Septuaginta; Budi Jejen Zaenal Abidin (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2020)
The internet is an important channel in the distribution of information and promotional activities for a university. Many information-seeking activities in society have shifted from conventional methods to digital. The website then becomes an important digital storefront for a university to distribute information and conduct promotional activities, including in this case, Institut Manajemen Wiyata Indonesia. Institut Manajemen Wiyata Indonesia has had a website from the time it was first established, but the existing website is considered too monotonous. Development and changes in interface design then need to be done. This effort begins with first conducting a 5W + 1H analysis to identify existing problems, decipher the background of the problem, to present alternative solutions. Follow-up observations and interviews are conducted with interested users to find out what expectations or content needs to be posted on the website. From this study it was concluded that the design of the user interface on the website must not eliminate its function as a medium in disseminating information to the public. Then the delivery of a strong identity that characterizes universities is done through informative media and supported by visual processing that emphasizes the quality and readability of the content when accessed from various types of user devices.